Why Utopia is Dead. A Blochian Introduction to the End of a Fiction - Gianluca Bonaiuti (Scienza & Politica, 2017)
The paper suggests a theoretical re-reading of Utopia. Usually dismissed as a pathological form of politics, it deals with the borders of modern political semantics and raises important issues about contemporary political theory. Bloch’s notion of Utopia helps to reframe the discussion about the ambiguous meaning of this term and introduce philosophical interpretations of this concept. Drawing from heterogeneous philosophical material (in particular Ernst Bloch’s theory of the «Possible» and Hans Blumenberg’s theory of «Fiction of Possibility»), it is argued that the problem of the death of Utopia arises when a particular form of subjective cognition, confronting contingency, is asked to open up for the prospect of progressive and democratic expectations. Utopia thus acquires an ambivalent position by articulating contemporary political reason.